2016
DOI: 10.4049/jimmunol.1501819
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular RIG-I Signaling Regulates TLR4-Independent Endothelial Inflammatory Responses to Endotoxin

Abstract: Sepsis is a systemic inflammatory response to infections associated with organ failure that is the most frequent cause of death in hospitalized patients. Exaggerated endothelial activation, altered blood flow, vascular leakage, and other disturbances synergistically contribute to sepsis-induced organ failure. The underlying signaling events associated with endothelial proinflammatory activation are not well understood, yet they likely consist of molecular pathways that act in an endothelium-specific manner. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 42 publications
6
33
0
1
Order By: Relevance
“…In addition, RIG-I knockdown inhibited LPS-mediated upregulation of VCAM-1 and E-selectin ( Fig. 4 b, c), confirming previous findings [13] , whereas IRF-1 knockdown only inhibited LPS-mediated VCAM-1 induction ( Fig. 3 b, 4 b).…”
Section: Rig-i Regulates Vcam-1 Expression In Part Bysupporting
confidence: 89%
See 4 more Smart Citations
“…In addition, RIG-I knockdown inhibited LPS-mediated upregulation of VCAM-1 and E-selectin ( Fig. 4 b, c), confirming previous findings [13] , whereas IRF-1 knockdown only inhibited LPS-mediated VCAM-1 induction ( Fig. 3 b, 4 b).…”
Section: Rig-i Regulates Vcam-1 Expression In Part Bysupporting
confidence: 89%
“…IRF-1 was shown to regulate basal transcription, as well as dsRNA-mediated upregulation of RIG-I [24] . Recent data from our laboratory showed that in endothelial cells, RIG-I is an intracellular receptor that regulates LPS-induced endothelial activation [13] . Based on these findings we hypothesized that IRF-1 was an upstream regulator of RIG-I- 554 mediated endothelial responses to LPS.…”
Section: Rig-i Regulates Vcam-1 Expression In Part Bymentioning
confidence: 99%
See 3 more Smart Citations